Assessing the viability of Black Soldier Fly larvae (Hermetia illucens) as an alternative fish feed in rearing fry of Nile tilapia (Oreochromis niloticus) - Villanueva, Aidan R. (Zamorano: Escuela Agrícola Panamericana, 2025)
Alternative feeds, such as black soldier fly (Hermetia illucens) larvae, are emerging as sustainable animal feed alternatives due to their efficient feed conversion, low resource requirements, and high nutrient content. Therefore, the objective of this study is to evaluate the inclusion of black soldier fly larvae on the performance of Nile tilapia fry in comparison to a conventional feed. Over 42 days a total of 600 tilapia fry with an average weight of 0.4 g were sourced after the sex reversion stage and distributed amongst 12 tanks in groups of 50. The study included a control diet and three experimental diets with larvae meal replacing 25%, 50%, and 75% of the conventional protein source. Samples were collected from each tank every seven days to assess the weight gain of the tilapia fry. A completely randomized experiment was done along with an ANOVA and Duncan mean test. The data analysis on the final mean weight and daily weight gain showed that the differences between the experimental diets were negligible (P > 0.10). However, there was a significant difference (P < 0.10) between the experimental diets and the control diet. There were no significant differences in specific growth rate, survival, and feed conversion ratio (P > 0.10). The results suggest that black soldier fly larvae meal can serve as an alternative protein source. Full conversion from conventional feed to fly larvae meal could enhance environmental sustainability, but further research is needed to evaluate the environmental impacts of larvae production and other alternatives.